Drip by precious drip - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Even when it is scarce, private initiative will always find its place, just like even scarce water will always rush to fill a dip. And so it was in the late 1980s in much of sub-Saharan Africa (SSA). Where there were irrigation systems in place,...